Change in Prevalence of Congenital Defects in Children With Prader-Willi Syndrome - Torrado, M. (2013)
OBJECTIVE: The aim of this study was to assess the prevalence of congenital defects observed in patients with Prader-Willi syndrome (PWS) and to compare this prevalence with that described in the general population. In addition, these findings were correlated with the different etiologic subtypes. METHODS: A total of 180 children with PWS followed for 13 years were included in this study. Diagnosis was confirmed by the methylation test, and genetic subtypes were established by using fluorescence in situ hybridization or multiplex ligation-dependent probe amplification and microsatellite analyses. The prevalence of congenital defects was compared with national and international registries of congenital defects in the general population (Estudio Colaborativo Latinoamericano de Malformaciones Congénitas, European Surveillance of Congenital Anomalies, and the New York Registry). RESULTS: Twenty-two percent of the patients presented congenital defects with a risk of 5.4 to 18.7 times higher than that of the general population. The most frequent congenital defects were heart defects, renoureteral malformations, vertebral anomalies, hip dysplasia, clubfoot, and agenesis/hypoplasia of the corpus callosum. Each of these congenital defects was significantly more frequent in the children with PWS than in the general population. The congenital heart defects were more frequent in girls than in boys with PWS. No significant differences were found when the defects were correlated with the different etiologic subtypes. CONCLUSIONS: An increased prevalence of congenital defects was found in our PWS patients. This finding suggests the need for further studies in PWS children that allow physicians to detect the congenital defects found in this series and, thus, to anticipate complications, with the ultimate aim of enhancing the management of PWS patients.